2015
DOI: 10.1186/1742-4755-12-s1-s3
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of maternal mortality on households: evidence from three sub-counties in rural western Kenya

Abstract: BackgroundThis study explores the consequences of a maternal death to households in rural Western Kenya focusing particularly on the immediate financial and economic impacts.MethodsBetween September 2011 and March 2013 all households in the study area with a maternal death were surveyed. Data were collected on the demographic characteristics of the deceased woman; household socio-economic status; a history of the pregnancy and health care access and utilization; and disruption to household functioning due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
1
20
1
3
Order By: Relevance
“…The economic household burden of maternal mortality in rural Kenya was studied by Kes et. al using mixed methods, with focus group discussions to illuminate the economic findings [ 17 ]. While transport, health care during the pregnancy, and delivery costs were high, it was the funeral costs that were the most monumental.…”
Section: Editorialmentioning
confidence: 99%
“…The economic household burden of maternal mortality in rural Kenya was studied by Kes et. al using mixed methods, with focus group discussions to illuminate the economic findings [ 17 ]. While transport, health care during the pregnancy, and delivery costs were high, it was the funeral costs that were the most monumental.…”
Section: Editorialmentioning
confidence: 99%
“…Equally so, in our study setting, the financial burden ranged beyond the acute in-hospital phase, involving kin and acquaintances and giving up business ambitions to make ends meet. With a growing body of work on (severe) maternal morbidity and with suggested strong links between poverty and poor health outcomes, as shown in economic studies on maternal mortality [30][31][32][33][34][35], the nexus between economic resources and maternal morbidity deserves to be assessed.…”
Section: The Financial Burdenmentioning
confidence: 99%
“…Maternal mortality, defined as the death of women during pregnancy, childbirth, or in the 42 days after birth, has negative impacts on household economic activity . Households may experience catastrophic health expenditures prior to the maternal death, increasing the risk the household will fall into poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Households may experience catastrophic health expenditures prior to the maternal death, increasing the risk the household will fall into poverty. A study in Kenya found that households that experienced a maternal death spent 30% of annual per‐capita consumption expenditure to cover costs including facility fees, transport, medicines, bedding, food, and hotel stay for the woman and people accompanying the woman to seek care …”
Section: Introductionmentioning
confidence: 99%